Notes on two rare conger eel species (Anguilliformes: Congridae) found in Taiwanese waters - Ho, Hsuan-Ching; Smith, David G.; Huang, Jian-Fu (Zootaxa, 2018)
Although Taiwan is a small island, it occupies a strategic biogeographic position between the faunal regions of Japan to the north and the Philippines to the south. As a result, it has an interesting mixture of northern and southern species. In this paper, we report new records of two species of congrid eel, one known previously from Japan and China, and the other known only from the Philippines. The first species, Promyllantor nezumi Asano, 1958, was described by Asano (1958) and reassigned to a newly established genus Acromycter by Smith & Kanazawa (1977). Zhang (1989) reported the species from east of Hainan Island, China. The second species, Gnathophis asanoi Karmovskaya, 2004, was described from the Philippines based on two types. Ho et al. (2015) reported one specimen collected from Taiwan but provided one additional specimen was collected more recently.